Luteinizing Hormone Release in Kisspeptin treated Pre- pubertal Murrah Buffaloes - Pandey, Himanshu; Nishant Kumar; Kumar, Dheeraj (The Indian Journal of Animal Reproduction, 2024)
Kisspeptin is a neuropeptide that governs the reproductive axis upstream to GnRH. Present study was undertaken tocompare the effect of different doses of kisspeptin on release of luteinizing hormone (LH) in Murrah buffaloes duringpre-pubertal period. Twenty four pre-pubertal buffalo heifers were selected and divided into 4 groups (Control, T1, T2and T3), having 6 animals in each group. Kisspeptin-10 was administered at the dose of 2 μg/kg body weight, 1.5 μg/kg body weight, 1μg/kg body weight respectively in T1, T2 and T3 group along with administration of equal volume ofNSS in control group. Blood sampling was done at every 20 minutes interval beginning with zero minutes up to 2 hoursand analyzed for LH concentration. Results indicated that LH concentration was significantly (p
Keywords: Buffalo; Kisspeptin; LH; Pre-pubertal